Genomic and Transcriptomic Characterization of Canine Osteosarcoma Cell Lines: A Valuable Resource in Translational Medicine - Gola, Cecilia; Giannuzzi, Diana; Rinaldi, Andrea; Iussich, Selina; Modesto, Paola; Morello, Emanuela; Buracco, Paolo; Aresu, Luca; De Maria, Raffaella (Frontiers in Veterinary Science, 2021)
Osteosarcoma (OSA) represents the most common primary bone tumor in dogs and is characterized by a highly aggressive behavior. Cell lines represent one of the most suitable and reproducible preclinical models, and therefore the knowledge of their molecular landscape is mandatory to investigate oncogenic mechanisms and drug response. The present study aims at determining variants, putative driver genes and gene expression aberrations by integrating whole-exome and RNA sequencing. For this purpose, eight canine OSA cell lines and one matched pair of primary tumor and normal tissue were analyzed. Overall, cell lines revealed a mean tumor mutational burden of 9.6 mutations/Mb (range 3.9-16.8). Several known oncogenes and tumor suppressor genes, such as ALK, MYC and MET, were prioritized as having a likely role in canine OSA. Mutations in 8 genes, previously described as human OSA drivers and including TP53, PTCH1, MED12, PI3KCA, were retrieved in our cell lines. When variants were cross-referenced with human OSA driver mutations, the E273K mutation of TP53 was identified in Wall cell line and tumor sample. The transcriptome profiling detected two possible p53 inactivation mechanisms in Wall cell line on one hand, and in D17 and D22 on the other. Moreover, MET overexpression, potentially leading to MAPK/ERK pathway activation, was observed in D17 and D22 cell lines. In conclusion, our data provide the molecular characterization of a large number of canine OSA cell lines, allowing future investigations on potential therapeutic targets and associated biomarkers. Notably, Wall cell line represents a valuable model to empower prospective in vitro studies both in human and in dogs, since the TP53 driver mutation was maintained during cell line establishment and was widely reported as a mutation hotspot in several human cancers.